Microscopic Investigation of Grain Boundaries in Organolead Halide Perovskite Solar Cells - Li, Jiang-Jun; Ma, Jing-Yuan; Ge, Qian-Qing; Hu, Jin-Song; Wang, Dong; Wan, Li-Jun (ACS applied materials & interfaces, 2015)
Grain boundaries (GBs) play an important role in organic–inorganic halide perovskite solar cells, which have generally been recognized as a new class of materials for photovoltaic applications. To definitely understand the electrical structure and behavior of GBs, here we present Kelvin probe force microscopy and conductive atomic force microscopy (c-AFM) measurements of both typical and inverted planar organolead halide perovskite solar cells. By comparing the contact potential difference (CPD) of these two devices in the dark and under illumination, we found that a downward band bending exists in GBs that predominantly attract photoinduced electrons. The c-AFM measurements observed that higher photocurrents flow through GBs when a low bias overcomes the barrier created by the band bending, indicating that GBs act as effective charge dissociation interfaces and photocurrent transduction pathways rather than recombination sites.